2017
DOI: 10.18261/issn.1504-7989-2017-01-02-04
|View full text |Cite
|
Sign up to set email alerts
|

Innvandrerarbeidskraftens innvirkning på produktivitet, lønnsnivå og lønnsomhet

Abstract: The use of immigrant labor in businesses within the accommodation sector correlates with reduced wage growth and increased profitability. This result suggests that businesses substitute their workforce towards cheaper labor without experiencing productivity losses, thus inducing increased profitability. The correlation between use of immigrant labor and reduced wage growth increases with company size. The same patterns are found in the restaurants and bars sector. The characteristics of companies and industrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…At the same time, high-income groups are likely benefitting from the presence of immigrants, as cheaper and more flexible labour potentially increase profits and wages (Hoen et al, 2018;Iversen et al, 2017). In future research, more detailed inequality measures, such as P90/P50 and P50/P10, are needed to explore these mechanisms and determine where the effect is strongest.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, high-income groups are likely benefitting from the presence of immigrants, as cheaper and more flexible labour potentially increase profits and wages (Hoen et al, 2018;Iversen et al, 2017). In future research, more detailed inequality measures, such as P90/P50 and P50/P10, are needed to explore these mechanisms and determine where the effect is strongest.…”
Section: Discussionmentioning
confidence: 99%
“…Another important insight from the research literature is that the characteristics of firms and industries influence the impact of ethnic diversity on productivity (Richard et al 2007;Iversen et al 2017). It is especially in competitive industries where innovation and the development of new products are important that ethnic diversity influences firm performance (Andrevski et al 2014).…”
Section: Diversity In Management and Industry Characteristicsmentioning
confidence: 99%
“…Nevertheless, studies have shown that organizations employ ethnic minorities as a staffing strategy to keep salaries low (Soni-Sinha & Yates 2013;Ortlieb & Sieben 2013). The use of immigrant labor correlates with increased profitability and reduced wage growth in firms (Iversen et al 2017). Even in organizations that promote and value ethnic diversity, minorities work in lower positions and have temporary jobs and lower salaries than the majority (Bendick et al 2010;Romani et al 2018).…”
Section: Firm Performance and Ethnic Inequalitymentioning
confidence: 99%
“…Liknende er også observert i andre bransjer. En studie fant for eksempel at overnattingsbedrifter brukte innvandrere for å skifte ut «arbeidsstyrken i retning av billigere arbeidskraft» for å oppnå økt lønnsomhet (Iversen, Aalen & Jakobsen, 2017) -men denne studien fant ikke liknende tendenser i serveringsbransjen. En annen studie fant at arbeidsgivere i hoteller og fiskeribedrifter foretrakk enkelte innvandrergrupper framfor norskfødte til bestemte typer jobber i virksomhetene (Friberg & Midtbøen, 2017).…”
Section: Hvilke Mekanismer?unclassified